2019
DOI: 10.1108/ejm-06-2017-0424
|View full text |Cite
|
Sign up to set email alerts
|

Consumption field driven entrepreneurship (CFDE)

Abstract: Purpose This study aims to explore how membership (initially as a consumer) in a given field shapes individuals’ entrepreneurial journey. Design/methodology/approach The research context is cultural and creative industries and, in particular, the independent (indie) music field in which unstructured interviews were conducted with nascent and established cultural entrepreneurs. Findings The authors introduce and justify their theoretical framework of consumption field driven entrepreneurship (CFDE) that cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…They intend to give to a group they toughly identify with and define success as delivering value to their community (Ko & Kim, 2020). Communitarians enact their identity by creating an entrepreneurial venture as they realize the products, they had designed for themselves are of interest to fellow community members (Daskalopoulou & Skandalis, 2019). Consequently, we hypothesize the following: Hypothesis 2b: Communitarian social identity influences positively entrepreneurial intention.…”
Section: Entrepreneurial Social Identities and Intentionmentioning
confidence: 99%
See 1 more Smart Citation
“…They intend to give to a group they toughly identify with and define success as delivering value to their community (Ko & Kim, 2020). Communitarians enact their identity by creating an entrepreneurial venture as they realize the products, they had designed for themselves are of interest to fellow community members (Daskalopoulou & Skandalis, 2019). Consequently, we hypothesize the following: Hypothesis 2b: Communitarian social identity influences positively entrepreneurial intention.…”
Section: Entrepreneurial Social Identities and Intentionmentioning
confidence: 99%
“…Communitarians consider themselves as entrepreneurs as long as they receive positive feedback and support form their fellow community members (Gruber & MacMillan, 2017) Daskalopoulou & Skandalis (2019) state that the relationship between consumer membership in a field and, the skills, competences, and community an entrepreneur has influence how communitarian entrepreneurs convert forms of non-material and material capital to create businesses. Communitarians identify with the worldview of their community and engage in consumption activities in the process of gaining entrepreneurial legitimation within a specific field.…”
Section: Entrepreneurial Social Identities Self-efficacy and Intentionmentioning
confidence: 99%
“…On the other hand, during the process, the vast majority of studies consider that using DTIC to perform interviews is a factor that reflects the context of the phenomenon or the investigated consumption practices (Dolbec & Fischer, 2015;Oakes et al, 2014). Likewise, several works are dedicated to exploring territorially dispersed phenomena, demanding that access to respondents is, at some level via electronic contact, to, for example, schedule a possible face-to-face meeting (Daskalopoulou & Skandalis, 2019;Emontspool & Georgi, 2016). Another very common type of work observed were those investigating phenomena that exist exclusively in the virtual context (Kozinets et al, 2016;Viswanathan & Sreekumar, 2019).…”
Section: Academic Usementioning
confidence: 99%
“…In turn, narrative studies (Bradshaw & Dholakia, 2012;Daskalopoulou & Skandalis, 2019;Figueiredo & Uncles, 2014;Jones et al, 2020;Viotto et al, 2021) use the method exclusively in their studies (Level 1). The narrative studies that we observed considered online interviews equivalent to face-to-face meetings in terms of wealth, but mainly allow interviewers and interviewees to conduct a process that is often long, from the comfort of their own homes.…”
Section: Research Strategymentioning
confidence: 99%
See 1 more Smart Citation